2002
DOI: 10.1002/pat.191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of liquid crystalline copolyesters containing horizontal and lateral rods in main chain

Abstract: A series of liquid crystalline copolyesters containing both horizontal and lateral rods in main chain were synthesized through solution polymerization of 2,5‐bis(4‐alkoxy benzoyloxy)hydroquinone, 4,4′‐dihydroxy‐α,ω‐diphenoxydecane and 4,4′‐dichloroformyl‐α,ω‐diphenoxydecane. These copolyesters were soluble in common organic solvents, showed thermotropic nematic liquid crystallinity that can be easily obtained at room temperature, thereby making them processable at relatively low temperatures in their high‐orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…4 and Table 4, which implies the existence of different crystalline states. Such phenomenon has been given much attention [44,45] and has been confirmed through DSC examinations at different heating rates [42]. From the data listed in Table 4, it can be found that the LC temperature range of the polymers became much narrower with the introduction of lateral rods in comparison with the parent polymer P 0 , which may be due to the decreased regularity of molecular alignment by the introduction of lateral rods.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…4 and Table 4, which implies the existence of different crystalline states. Such phenomenon has been given much attention [44,45] and has been confirmed through DSC examinations at different heating rates [42]. From the data listed in Table 4, it can be found that the LC temperature range of the polymers became much narrower with the introduction of lateral rods in comparison with the parent polymer P 0 , which may be due to the decreased regularity of molecular alignment by the introduction of lateral rods.…”
Section: Resultsmentioning
confidence: 85%
“…We have reported the design and synthesis of a series of LC copolyesters potentially having auxetic behaviour [42], their solubility and phase transition temperatures could be well adjusted by changing the ratios of the horizontal and lateral rods. The introduction of lateral rods decreases the molecular regularity and nematic stability, while the nematic feature of the polymers can be easily retained at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous reports of laterally linked mesogens of high molar mass. [1][2][3][4][5][6][7] The meta linkage was chosen here because it could, in principle, produce a 908 angle between the pentaphenyl rod and the chain direction in the fully extended chain case.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon of multiple melting was reported in many papers as a feature in common for liquid crystalline polyesters. [8,10,[37][38][39] The multiple melting behavior has been previously attributed to reasons including the presence of different crystal structures, [40,41] or to crystal reorganization, [42,43] or to different components of the morphology formed in multiple stages of crystallization. [44] DSC traces of polymers 4a-4d have similar features.…”
Section: Thermal Analyses: Thermal Transitionsmentioning
confidence: 99%